Short selling recall option pricing: empirical and theoretical approaches - Almeida, Leonardo Viana de (2016)
Short selling is important for price efficiency as it helps negative information to be incorporated into prices. As short selling requires borrowing stock in advance, the equity lending market plays a central role in price efficiency. For instance, when the costs of borrowing certain equities are high, these stocks are likely to be overpriced. Unfortunately, not much is known about the equity lending market, particularly the Brazilian market. Here, we have investigated a particular feature of the equity lending contract, namely, the lender recall option. Lending contracts either i) allow the lender to recall the stock at an earlier date than initially agreed, or ii) allow no early recall, that is, they are fixed term contracts. We have derived a simple model for recall option pricing and confirmed the model empirically